2009
DOI: 10.1021/jf9007696
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effects on the Stability and Antioxidant Activity of an Acid Polysaccharide Conjugate Derived from Green Tea

Abstract: A technique of high-performance gel permeation chromatography (HPGPC)-evaporative light-scattering detection and circular dichroism (CD) was developed for the measurement of thermal effects on the homogeneity and conformation of polymeric carbohydrate conjugates and was applied to an acid polysaccharide conjugate (GTa) isolated from the composite enzyme extract of green tea. Incubations in water at 40 and 70 degrees C for 1.0, 2.5, and 5.0 h have no effects on GTa. In contrast, when incubated in water for 1.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 14 publications
0
26
0
3
Order By: Relevance
“…The scavenging potency of these crude TPS for the self-oxidation of 1,2,3-phentriol of all samples was evaluated according to Marklund method [22].…”
Section: Self-oxidation Of 123-phentriol Assaymentioning
confidence: 99%
“…The scavenging potency of these crude TPS for the self-oxidation of 1,2,3-phentriol of all samples was evaluated according to Marklund method [22].…”
Section: Self-oxidation Of 123-phentriol Assaymentioning
confidence: 99%
“…Several investigations have demonstrated that plant polysaccharides have hypoglycemic activity [16][17][18]. M. charantia (Bitter melon) of family (Cucurbitaceae) is a herb grown in South Asia and is well-known as an anti-inflammatory, anti-tumor, antiviral, hypo-lipidemic and as anti-diabetic agent [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The best known are the catechins, or flavonoids, or polyphenolic compounds, but it contains also polysacharide conjugates (TPCs), amino acids, caffeine and vitamins (Fujihara et al, 2007;Monobe et al, 2008;Chen et al, 2009). …”
Section: Introductionmentioning
confidence: 99%